Selection signatures in candidate genes and QTL for reproductive traits in Nellore heifers - Montes, Donicer E. [UNESP]; Braz, Camila U. [UNESP]; Ribeiro, André M.F. [UNESP]; Cavani, Lígia [UNESP]; Barbero, Marina M.D. [UNESP]; Albuquerque, Lucia G. [UNESP]; Curi, Rogério A. [UNESP]; Oliveira, Henrique N. [UNESP] (Elsevier, 2019)
The identification of selection signature genes may help to detect genomic regions that underwent artificial selection and contributed to phenotypic diversity. The aim of this study, therefore, was to detect selection signatures in candidate genes and quantitative trait locus (QTL) for reproductive traits in a Nellore population being selected for sexual precocity. A total of 2035 Nellore heifers, sourced from breeding programs focused on sexual precocity, were used. Candidate genes and some specific QTL related to reproductive traits were chosen based on published literature and Animal QTL databases, respectively, for investigation whether these regions were affected by selection. Selection signature DNA sequences were detected in the selected regions using the extended haplotype homozygosity (EHH) and relative extended haplotype homozygosity (REHH) methods. From 22,241 single nucleotide polymorphisms (SNPs) located in the candidate genes and QTL, 17,312 SNPs generated 2756 haplotype blocks. A total of 7518 EHH tests were analyzed using haplotypes with a frequency of more than 25%, for which there were 39 tests that were significant for REHH (P<0.01). Selection signature DNA sequences were detected that contained several QTLs for important reproductive traits in cattle, suggesting that reproductive traits may have been affected by selection for sexual precocity in this population. Forty-six genes were located in the selection signature regions, whereas 24 genes participated in important biological processes or pathways that may underlie sexual precocity. These results indicate there are possible molecular mechanisms related to sexual precocity in the Nellore breed.
Keywords: Beef cattle; Bos indicus; Relative extended haplotype homozygosity; Sexual precocity; Single nucleotide polymorphisms